Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2482-13-s2-s8
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymphadenectomy for breast cancer in elderly patients and fibrin glue

Abstract: BackgroundAxillary lymphadenectomy or sentinel biopsy is integral part of breast cancer treatment, yet seroma formation occurs in 15-85% of cases. Among methods employed to reduce seroma magnitude and duration, fibrin glue has been proposed in numerous studies with controversial results.MethodsThirty patients over 60 years underwent quadrantectomy or mastectomy with level I/II axillary lymphadenectomy; a suction drain was fitted in all patients. Fibrin glue spray were applied to the axillary fossa in 15 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 35 publications
(35 reference statements)
3
14
0
6
Order By: Relevance
“…In the present study, we found a signi cant decrease in the total volume of aspirated uid in the group who received brin glue compared to the control. This nding is in accordance with the results documented by other authors who used commercial brin glue in their interventions [5,[7][8][9]. However, con icting results were found by other authors, who reported inconclusive results or even harmful effects of brin glue which were explained by the presence of drains that may interfere with the maturation of the brin clot and the blockage of the lymphatic vessels [16][17][18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we found a signi cant decrease in the total volume of aspirated uid in the group who received brin glue compared to the control. This nding is in accordance with the results documented by other authors who used commercial brin glue in their interventions [5,[7][8][9]. However, con icting results were found by other authors, who reported inconclusive results or even harmful effects of brin glue which were explained by the presence of drains that may interfere with the maturation of the brin clot and the blockage of the lymphatic vessels [16][17][18].…”
Section: Discussionsupporting
confidence: 90%
“…Fibrin glue, light-activated brin sealant, and transdermal photopolymerized adhesive have been associated with reduction in the uid build-up post mastectomy through various studies [6][7][8][9]. Fibrin glue acts by lessening the number of disrupted lymphatics and minute vessels during axillary dissection hence resulting in lowering of seroma output [6,10] and provide hemostasis by controlling the hematomas which may delay wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been proposed in order to reduce seroma formation, such as external compression dressing [37], drainage placement [38][39][40][41], usage of fibrin glue [42,43], flap fixation and obliteration of the dead space [44], unfortunately with inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…In 9 patients, we used fibrin glue to reduce postoperative lymphorrhea, but it was not used in this case. Several prospective studies have addressed the use of a fibrin sealant to reduce lymphadenectomy-related postoperative complications in patients undergoing dissection of the groin, axilla, or paraaortic lesions [2122232425]. However, these results remain controversial.…”
Section: Discussionmentioning
confidence: 99%